Educar para o pensamento crítico: um estudo sobre a teoria de Adorno aplicada à educação - Marins, Alexandre Ricardo (2013)
The contemporary world has been facing many social contradictions associated with deep and overwhelming crises. As a result of such crises, we can observe a growing disengagement with the process of emancipatory humanization, in other words, instead of an emancipated consciousness, there is in fact a strengthening of oppressive, deteriorating conditions concerning life and human dignity. Besides all the problems caused by such crises, education has also suffered the oppression imposed by the ruling classes which try to impose their ideologies through educational programs that alienate and legitimize the maintenance of the status quo according to their concerns. Abandoning the commitment to reflection and the domain knowledge, school politics began to support this scenery. Facing these issues, and based on the ideas of Theodor Adorno, this dissertation analyzes Adorno s views about the meaning and scope of critical thinking for human emancipation, identifying the alienation elements in the educational environment that prevent such emancipation. We also discuss his ideas to overcome them. To develop this study, we worked with a qualitative research, applied on a group of graduating high school students from a model public school in the State of Minas Gerais. As a result, we present a discussion of the most important topics we came across: the relationship between alienation, education and work; the dialectics concerning the reified consciousness; the relationship between education and power; the role of critical thinking in education